Investigating lexical variation and change in Malaysian twitter : a conceptual paper - Noraishah Gulnazir,; Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Social media platforms such as Twitter is constantly transforming the usage of lexical items among global Internet users, including in Malaysia. Interestingly, despite adopting British English in the national education system, American English is gaining prominence among Malaysians due to the widespread dissemination of American English through the media. American English has been classified as a hyper-central language, serving as the hub for global English in Mair’s theory of The World System of Englishes. Despite of the magnitude of American English as a global language, there is a dearth of research on how American English is affecting other varieties of English, especially Malaysian English. There is a need to examine the role of American English in leading global language variation and change. Thus, this conceptual paper proposes how the influence of American English on Malaysian English, in terms of lexical items can be investigated on Twitter. This paper demonstrates how two emerging American lexical items lit and on fleek can be investigated in terms of its trend of frequency and patterns of usage in Malaysian Twitter through a number of tools and methods. Results from such a study may be able to reveal the extent to which Malaysian English is influenced by American English in terms of lexical units on Twitter, shedding light on the global transformation of the English language.